The first fowler : a green ember story - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith) Green ember (Series), 2019)
"In this sequel to The Last Archer, Jo Shanks is back in action against the Preylord tyrants. Alongside Helmer and Emma, this riveting adventure sees Jo on a perilous journey where survival and the cause itself are at stake. Faced with a calamitous quandary, the loyal band of rabbits must break out of a fatal trap and survive to breathe life into the fledgling resistance. An heir in peril. An archer hunted from the skies. Who will hunt the hunter?"--Amazon website.